Tax Absence in Relation to Taxation of Digital Services - Čejková, Tereza (Public Governance, Administration and Finances Law Review, 2021)
In the area of taxation of business corporations operating in several different countries, there is a problem arising with he identification of the tax residence of the liable entity. With the expansion of the so-called digital business, where entrepreneurs often do not have a physical headquarters or business units, this problem is becoming more common. Efforts to introduce a digital tax within the Member States of the Organisation for Economic Co-operation and Development and the European Union are accompanied by efforts to address this issue through various legislative acts. This article explains how the problem of identifying tax residence arises, why it is undesirable and describes possible solutions.